A independência jurídica do notário e do registrador - Pinho, Ruy Veridiano Patu Rebello (2018)
The purpose of this dissertation is to emphasize the existence of the duty of legal independence of the registrar and the notary, who are responsible of a legal function constitutionally decentralized by the Charter of 1988 and disciplined by Law 8935/94, the Law of Notaries and Registrars. Independence is not a state of the person, but takes place contemporaneously in an argumentative intersubjective process of cooperative order. This mechanism of decentralization of powers and competences outside the structure of the State, gives an independent legal professional a bundle of legal responsibilities to be exercised through an administrative and technical organization, so that along legal independence, that all legal profession implies, goes the management and administration of its resources under private law. Every legal function must be accountable to the society and to be supervised; by law, the inspection and technical standardization of the services is attributed to the Judiciary. In order to concentrate the finite judicial powers in its nuclear activity, the Judiciary has an important role in ensuring the legal independence of the registrar and the notary as legal duties to society